Quantum dynamics study of singlet-triplet transitions in s-trans-1,3-butadiene - Nikoobakht, Behnam; Köppel, Horst (Chemical physics letters, 2016)
The intersystem crossing dynamics of s-trans-1,3-butadiene in its lowest singlet and triplet states is studied theoretically, employing a fully quantal approach for the first time. The electronic states 21Ag, 11Bu, 13Bu and 13Ag, which interact vibronically and via the spin-orbit coupling are treated in the calculation, thus covering the lowest spin-forbidden electronic transitions. Up to five nuclear degrees of freedom, including out-of-plane dihedral angles are included in our investigation. The calculation of potential energy surfaces relies on the CASPT2 method, and the evaluation of spin-orbit coupling matrix elements using the full two-electron Breit-Pauli Hamiltonian is performed by utilizing the MRCI wavefunction. The latter dependence on the nuclear coordinates is included for the first time. An electronic population transfer on the sub-picosecond time scale due to intersystem crossing is obtained, a mechanism that can contribute to the singlet-triplet transitions in the electron energy loss spectrum of s-trans-1, 3-butadiene. It is found that the dependence of the spin-orbit coupling on the out-of-plane coordinates plays a dominant role in these singlet-triplet transitions. The amount of population transfer to the 13Ag and 13Bu states is roughly of the same order of magnitude.